DAPE cloning with modified primers for producing designated lengths of 3’ single-stranded ends in PCR products - Seoee Lee; Hyunyoung Kim; Aqsa; Kwangjin Jeung; Minho Won; Hyunju Ro (PLoS ONE, 2025)
For in vitro DNA assembly, enzymes with exonuclease activities have been utilized to generate relatively long recessed ends on DNA fragments, which can anneal to other DNA fragments if they have complementary nucleotide sequences. The combined construct can be directly delivered to competent cells, where the gaps and nicks between the fragments are completely rectified. We introduce a versatile sequence- and ligation-independent cloning (SLIC) method called ’DNA Assembly with Phosphorothioate (PT) and T5 Exonuclease’ (DAPE), which generates precise lengths of 3’ overhangs at both ends of linearized DNA. In contrast to conventional SLIC techniques, which are not suitable for cloning DNA fragments smaller than 50 base pairs (bp) due to overzealous exonuclease activity, such as with gRNA and epitope tags, DAPE can efficiently and precisely assemble several fragments in a single reaction regardless of the size of the DNA. Thus, DAPE, as an advanced toolkit for DNA cloning and synthetic biology, may further expedite the construction of more elaborate multi-gene circuitry.